Sound-encoded faces activate the left fusiform face area in the early blind. - Paula L Plaza; Laurent Renier; Stephanie Rosemann; Anne G De Volder; Josef P Rauschecker (PLoS ONE, 2023)
Face perception in humans and nonhuman primates is accomplished by a patchwork of specialized cortical regions. How these regions develop has remained controversial. In sighted individuals, facial information is primarily conveyed via the visual modality. Early blind individuals, on the other hand, can recognize shapes using auditory and tactile cues. Here we demonstrate that such individuals can learn to distinguish faces from houses and other shapes by using a sensory substitution device (SSD) presenting schematic faces as sound-encoded stimuli in the auditory modality. Using functional MRI, we then asked whether a face-selective brain region like the fusiform face area (FFA) shows selectivity for faces in the same subjects, and indeed, we found evidence for preferential activation of the left FFA by sound-encoded faces. These results imply that FFA development does not depend on experience with visual faces per se but may instead depend on exposure to the geometry of facial configurations.